Associations Between Effort Capacity and Cognitive Processes in Basketball Players - Maria-Andreea COTEAȚĂ; Florin TROFIN (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae)
Introduction: The game of basketball often involves making quick and efficient decisions and complex technical-tactical actions, which have been shown by researchers to correlate with certain cognitive processes. Objective: We aimed to determine this link in a group of 21 basketball players (14.05±0.86 years old) who qualified for the U14 Final Tournament of the Romanian National Championship. Methods: We associated 3 types of visual memory (simple, dynamic and numerical) with 3 agility tests (Lane, Illinois, hexagon with randomized visual stimuli), 1 reaction speed test, 1 aerobic (Vameval shuttle) and 1 anaerobic (8x10+10 m) test and the test for determining the explosive force of the lower limbs. Results: Data analysis yielded 2 links between effort capacity and players’ cognitive level. Numerical memory was correlated with the Lane agility test (p=0.041), and the reaction speed of the dominant upper limb with the fatigue factor yielded by the anaerobic lactacid capacity test (p=0.05). Conclusions: Our study demonstrates that an athlete with a significant exertional capacity does not require a high cognitive level, this aspect needs to be demonstrated by future research.